Quality as perceived by nursing professionals in an accredited specialized hospital - Luis Roberto Barbino Junior; Larissa Gutierrez de Carvalho e Silva; Carmen Silvia Gabriel
ABSTRACT Objective: To identify quality of service in an accredited specialized hospital according to nursing professionals' expectations and perceptions. Method: This is a cross-sectional quantitative study with the participation of 34 employees, conducted from August to October 2017 by administration of an adapted and validated version of the SERVQUAL scale. Results: The interviewees reported as their highest expectations the transmission of confidence and provision of safe services, the latter also turning out to be the best perception of service. Promotional materials were considered as the least important expectation. The perception with the lowest scores was related to the time of service delivery at the institution, which may be associated with specific factors. Safety of service was considered as the quality dimension with greater relevance. Conclusion: It is highlighted the importance of measures for maintenance of schedules and preservation of good forms of promotion, communication and team training.